Direct effect of metformin on healthy ovarian cells - Velazquez, Candela (2019)
Metformin (MET) is an oral antihyperglycemic drug introduced in the treatment of polycystic ovary syndrome (PCOS) to manage hyperglycemia. PCOS is a common disorder that affects women in reproductive age. MET improves ovulation, pregnancy and live birth rates in patients with PCOS. The mechanism by which MET of these effects are not fully understood. MET primary mechanism of action is through the activation of the AMP-activated protein kinase (AMPK), which acts as an energy sensor within the cell. The aims of the present work were to analyze a possible effect of MET on healthy rat ovary and on granulosa cells (GCs) in culture. Methods: For in vivo experiments, 21 d old female Sprague Dawley rats received MET (300 mg/kg) dissolved in the drinking water for 15 days (MET group). The control group received drinking water alone. Rats were killed on day 16 and the ovaries removed. Proteins were extracted for western blot analysis. For in vitro experiments, Sprague Dawley rats (21 d) were injected subcutaneously with diethylstilbestrol (1mg/rat) daily for three days. GCs were isolated by percoll gradient. GCs were stimulated with MET (0.01 ng/ml) with or without the organic cation transporter (OCT) inhibitor cimetidine (CIM). Cells were harvested 48 h later and prote ins extracted. One Way ANOVA or t-test were used. p-AMPK was increased in the rat ovaries (p<0.05) and in GCs after stimulation with MET (p<0.05) while VEGF was decreased (p<0.05). Inhibition of OCTs by CIM reversed these effects (p<0.05 compared with MET). No changes in Angiopoietin 1 and 2 were found either in vivo or in vitro. Our results suggest that MET acts directly on ovarian cells regulating cell metabolism and VEGF expression, entering the cells through OCTs. Our findings are relevant to optimize PCOS fertility treatment and to explore direct ovarian MET actions in other female pathologies. These results provide new evidence to explain the effect of MET on infertility treatments.